Menurunkan Infertility-Related Stres dengan Program Mindfulness Based Stress Reduction (MBSR) - Diah Widiawati Retnoningtias; I Rai Hardika (Universitas Islam Indonesia, 2021)
Previous research has found that women with infertility feel sad, anxious, and stressed when undergoing medical interventions to have children. The purpose of this study was to see the effect of mindfulness based stress reduction(MBSR) in reducing infertility stress. This research was conducted with an experimental method. This study consisted of five (5) participants as the experiment group and five (5) participants as the control group, which were selected by purposive sampling technique. The characteristics of the research partcipants were married women for at least one (1) year and experienced infertility. The results showed that there was no significant difference between the posttest scores and the pretest scores in the experimental group. The results also showed that there was no significant difference between the posttest infertility stress scores of the experimental group and the control group posttest scores.